2019
DOI: 10.11648/j.ijfbr.20190504.13
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Board Diversity and Corporate Financial Performance: <i>Empirical Evidence from Five Selected Commercial Banks in Nigeria</i>

Abstract: The purpose of this research was to investigate the nature of the relationship between board diversity and financial performance of deposit money Banks quoted on the Nigerian stock exchange. Based on extensive review of the literature, three board diversity variables were identified namely gender (measured by the proportion of women in the boardroom), non-executive directors (measured by the proportion of non-executive directors that make up the boardroom) and board size. Financial performance was measured usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…So, we can validate our first hypothesis, which highlights the negative impact of board size on Moroccan banks' performance. Our results are consistent with (Cyprian Onyekwere et al, 2019;Eisenberg et al, 1998;Jensen, 1993;Sbai & Meghouar, 2017;Yermack, 1996) and contradict those of other authors Belkebir et al, 2018;Chenini & Jarboui, 2016).…”
Section: Table 6 Dynamic Panel Regression Results Using Gmm Eglssupporting
confidence: 90%
See 1 more Smart Citation
“…So, we can validate our first hypothesis, which highlights the negative impact of board size on Moroccan banks' performance. Our results are consistent with (Cyprian Onyekwere et al, 2019;Eisenberg et al, 1998;Jensen, 1993;Sbai & Meghouar, 2017;Yermack, 1996) and contradict those of other authors Belkebir et al, 2018;Chenini & Jarboui, 2016).…”
Section: Table 6 Dynamic Panel Regression Results Using Gmm Eglssupporting
confidence: 90%
“…shows that banks with a higher number of independent directors perform better during the crisis. Some authors (Coles et al, 2008;Khanchel El Mehdi, 2007;Zakaria et al, 2018) assert that independent directors' significant presence improves a company's performance. Likewise, Basuony et al (2014) found a significant relationship between the independent directors' presence and the financial performance of 50 banks in the Arabian Peninsula in 2011.…”
Section: Administrators' Independence and Performancementioning
confidence: 99%
“…To put it in a nutshell, firms should understand that the higher the diversity on the board, the more the opportunities to access finances cheaply and safely due to more effective supervision and decisions from the diverse board, and thereby reduces financial constraints problems, leading improvement in performance of the firm. This result supports outcomes from previous research such as (Sixtus et al, 2019). However, it was observed from the descriptive analysis that many firms still maintain less than the 30% diversity proposed by regulatory agencies as a threshold to achieving effectiveness of the board.…”
Section: Discussionsupporting
confidence: 89%
“…Abad et al (2017) stated that Norway and Spain mandated 40% female members on boards, and businesses that met this requirement were given preference in the awarding of government contracts, while there would be no official consequences. In order to increase board effectiveness, female directors employ board development tools like work instructions, assessments, and development programmes to lower conflict levels on corporate boards (Onyekwere et al, 2019). In another point of view, Azmi and Barrett (2013) asserted that women are more cautious, risk-averse, possess better knowledge about accounting and finance, and effective decision-makers.…”
Section: Concept Of Corporate Governance Attributesmentioning
confidence: 99%
“…Numerous scholarly studies show a positive relationship between WOB and bank financial success, implying that more diverse boards bring a wide range of perspectives, values and views, as well as more valuable resources, which improve bank financial performance. Bukar and Ahmed (2020), García-Meca et al (2015), Onyekwere et al (2019) and Uyar et al (2022), for example, illustrate that gender diversity enhances governance and report a favourable association between WOB and bank performance. Baselga-Pascual and Vähämaa (2021), Bhatia and Gulati (2021), Dong et al (2017), Jabari and Muhamad (2020), Mateus and Belhaj (2016), and Stefanovic and Barjaktarovic (2020) concluded that banks perform better when there are more women on bank boards.…”
Section: Women On Board and Bank Performancementioning
confidence: 99%